Peran Tabungan Bank Digital dalam Meningkatkan Literasi Keuangan Generasi Muda pada Era Transformasi Ekonomi Digital (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the implications of affective, cognitive, psychomotor, moral, and spiritual development in the learning process of a fourth-grade elementary school student. Using a descriptive qualitative approach, the research data were obtained through an interview with a student named Syakilla Mentari, who lives with her father, Ponimen, and her grandmother, Saminem. The findings show that Syakilla demonstrates strong emotional regulation; when she becomes angry, she remains silent and avoids expressing excessive emotions. Cognitively, she tends to study independently, even though she finds certain subjects, such as Mathematics and English, challenging. In contrast, she shows a high interest in religious subjects, particularly Aqidah. Psychomotor aspects are reflected in her active participation in daily household activities, especially assisting her grandmother after school. Morally and spiritually, Syakilla displays responsible behavior, respect for elders, and adherence to religious values in her everyday life. Overall, the results of this mini research indicate that the student’s developmental aspects contribute significantly to shaping her learning behavior, attitude, and personal character both at school and at home.